Challenges and Opportunities for School Administrative Staff in the Future - Nafi'a, Dinda Rahma; Imron, Ali; Mustiningsih, Mustiningsih (Proceedings Series of Educational Studies, 2024)
This article discusses the challenges and opportunities faced by school administrative staff in preparing for future modernization. The main issue highlighted is how modernization, particularly in the context of information and communication technology, affects the roles and responsibilities of school administrative personnel. The aim of this study is to identify the new skill requirements needed by administrative staff to adapt to these changes. The research methods used include qualitative analysis through interviews with administrative staff and direct observations at several educational institutions. The findings show a gap between the current skills possessed by administrative staff and those needed to meet the challenges of modernization. The conclusion of this article emphasizes the importance of ongoing training and professional development for school administrative personnel so that they can function effectively in an increasingly complex and technology-based educational environment.